(untitled) (International relations and international law Journal, 2024)
In this scientific article, current issues of legal application in the implementation of the "Global Zero" concept within the principle of disarmament are analyzed. The aim of the study is to identify legal obstacles in the realization of the "Global Zero" concept aimed at complete nuclear disarmament and to propose ways to overcome them. During the research, theoretical and practical aspects of disarmament principles in international law were examined. The main idea is the necessity to improve the international legal system to create a world free of nuclear weapons. The scientific and practical significance of the work is associated with developing proposals aimed at accelerating the disarmament process. The study employed methods such as analysis, comparative legal method, historical, and systemic analysis. The main results identified issues like incomplete implementation of international legal norms, the stance of nuclear powers, insufficiency of control mechanisms, and lack of political will. The conclusions of the study contribute to the improvement of legal application in the field of disarmament. The results have practical significance for forming disarmament policies of international organizations and states. The practical value lies in facilitating the creation of a world free from nuclear weapons through the implementation of the proposed measures. Key words: global zero, disarmament, law enforcement, concept, international security, nuclear disarmament, disarmament, international relations.